REFLECTION OF METHODOLOGIES OF EDUCATIONAL RESEARCH: DOES ACTION RESEARCH EXPERIENCED BY THE STUDENTS AFFECT LEARNING DEVELOPMENT AND SHIFTED MINDSET ON RESEARCH OF EDUCATION? - Abdul Halim; Wei-Shan Chang (Education Human and Development Journal, 2021)
Abstract: This paper reports reflections of one of the courses I took in this semester namely Methodologies of Educational Research. To construct this paper, I used qualitative biographical-reflective method which is aligned with interpretive paradigm of narrative inquiry research methodology to describe my own experience in the learning process. The data I used were the postings from Zuvio mobile application designed for advising learning process with online platform and personal experience from reflective process of the course. I analyzed the data with three-stage qualitative data analysis: data reduction, data display, and conclusion. The findings report that the classroom undergone with classroom action research has successfully overcome the difficulty faced by professors and students at international PhD programs. The students were found to perceive positive attitudes towards the carefully selected instructions design of action research with Flipped-Jigsaw approach. The implications were also proposed.